단순 원판형 평면 3자유도 액추에이터 설계 - 백두진; 김승종; 김하용 (한국소음진동공학회, 2005)
A disk-type 3-DOF actuator which has new principle and very simple structure is proposed. Also it utilizes the relation of bias and control fluxes produced by permanent magnets and coils, respectively, like other conventional electromagnetic actuators, but its main feature is that both the coils and permanent magnets are fixed in the stator, which makes it easy to design the shape of moving part. Operating principle is that a moving disk is driven by reaction force of Lorentz force acting on the fixed equivalent coil. Simple analytic approach and FEM analysis are performed to determine the design parameters so as to increase the driving force and distance. And some experimental results show the feasibility of the proposed actuator.